Exploring the mitogenomic of Lottiidae (Patellogastropoda): phylogenetics, gene rearrangement and evolutionary divergence time estimations - Jiantong Feng; Jing Miao; Jiji Li; Yingying Ye (BMC Genomics)
Abstract Background Lottiidae (Gray, 1840) is a derived family of Patellogastropoda and an important component of intertidal benthic communities. The mitochondrial genome (mitogenome) has been frequently used to analyze the phylogenetic relationships of Patellogastropoda. We used next-generation sequencing (NGS) to sequence the complete mitogenomes of five species. We analyzed the basic base composition characteristics of these mitogenomes, constructed a phylogenetic tree, compared the characteristics of gene rearrangement with other related species, and discussed the evolutionary patterns between gastropod species and the evolutionary relationships of each subclass. In addition, we aim to infer the differentiation time and evolutionary characteristics of various species in the order Patellogastropoda. These results will enrich the mitogenome database of Patellogastropoda and enhance our understanding of the genetic characteristics of Lottiidae and the phylogenetic relationships between gastropods. Results We obtained the mitogenomes sequences of Lottia peitaihoensis, Patelloida saccharinoides, Patelloida ryukyuensis, Nipponacmea sp. and Nipponacmea nigrans, using next-generation sequencing technology. We analyzed the basic structural characteristics of their mitogenomes and found that their lengths ranged from 16.6 kbp to 19.1 kbp. While N. nigrans and P. saccharinoides contain 39 genes, L. peitaihoensis, P. ryukyuensis, and Nipponacmea sp. have only 38 genes, with one trnW less. The most abundant base among the five species is T, and most protein coding genes (PCGs) use ATT, ATG, and ATA as starting codons, and TAA and TAG as stopping codons. We selected the mitogenomes of 10 Lottiidae species for selection pressure analysis and found that all PCGs were subject to purifying selection. Phylogenetic analysis indicates that Patellogastropoda is a fundamental branch of the Gastropoda, and Lottiidae, within Patellogastropoda, is an independent branch at the outermost of the entire phylogenetic tree. Comparison of mitochondrial gene sequences of all Patellogastropoda species revealed a high degree of gene rearrangement within the family Lottiidae, eight sequences present among the 10 species examined. By estimating their divergence times, we found that the divergence of limpets occurred as early as the Permian period of the Paleozoic Era, and a large number of species diverged in the Cenozoic Era. Conclusion The data obtained from this study will provide information on the assembly of the mitochondrial genome of the Lottiidae species, which will contribute to a better understanding of the evolutionary status and relationship among thes family of Patellogastropoda.